a/b=c/d
cmr : a)a-b/b = c-d/d
b)a/a+b = c/d+c
c)a/b-c=c/d-c
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 1
Ta có : \(\frac{a}{b}=\frac{c}{d}=>\left(\frac{a}{b}+1\right)=\left(\frac{c}{d}+1\right)\left(=\right)\frac{a+b}{b}=\frac{c+d}{d}\)
=> ĐPCM
Câu 2
Ta có \(\frac{a}{b}=\frac{c}{d}=>\frac{b}{a}=\frac{d}{c}=>\left(\frac{b}{a}+1\right)=\left(\frac{d}{c}+1\right)\left(=\right)\frac{b+a}{a}=\frac{d+c}{c}=>\frac{a}{b+a}=\frac{c}{d+c}\)
=> ĐPCM
Câu 3
Câu 3
Ta có \(\frac{a+b}{a-b}=\frac{c+d}{c-d}\)(=) (a+b).(c-d)=(a-b).(c+d)(=)ac-ad+bc-bd=ac+ad-bc-bd(=)-ad+bc=ad-bc(=) bc+bc=ad+ad(=)2bc=2ad(=)bc=ad=> \(\frac{a}{b}=\frac{c}{d}\)
=> ĐPCM
Câu 4
Đặt \(\frac{a}{b}=\frac{c}{d}=k\)
\(=>\hept{\begin{cases}a=bk\\c=dk\end{cases}}\)
Ta có \(\frac{ac}{bd}=\frac{bk.dk}{bd}=k^2\left(1\right)\)
Lại có \(\frac{a^2+c^2}{b^2+d^2}=\frac{b^2k^2+c^2k^2}{b^2+d^2}=\frac{k^2.\left(b^2+d^2\right)}{b^2+d^2}=k^2\left(2\right)\)
Từ (1) và (2) => ĐPCM
Đặt a/b=c/d=k
=>a=bk; c=dk
a: \(\dfrac{a-b}{b}=\dfrac{bk-b}{b}=k-1\)
\(\dfrac{c-d}{d}=\dfrac{dk-d}{d}=k-1\)
Do đó: \(\dfrac{a-b}{b}=\dfrac{c-d}{d}\)
b: \(\dfrac{a}{a+b}=\dfrac{bk}{bk+b}=\dfrac{k}{k+1}\)
\(\dfrac{c}{c+d}=\dfrac{dk}{dk+d}=\dfrac{k}{k+1}\)
Do đó: \(\dfrac{a}{a+b}=\dfrac{c}{c+d}\)